2015
DOI: 10.1002/ejsp.2092
|View full text |Cite
|
Sign up to set email alerts
|

When and why is helping others good for well‐being? The role of belief in reciprocity and conformity to society's expectations

Abstract: This research investigates the relation between informal help and subjective well-being and its underlying mechanisms using a cross-national perspective. We focus on two potential mechanisms derived from the self-determination theory and conformity to the social norms literature. From the standpoint of self-determination theory, helping others is good for well-being if it is intrinsically motivated, rather than driven by the expectation of reciprocity. On the other hand, from the perspective of the conformity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 77 publications
2
42
0
2
Order By: Relevance
“…Tian, Du, and Huebner (2015) revealed that altruistic behaviour was positively correlated with life satisfaction and positive affect. Findings reported by several empirical studies have also shown that altruistic behaviour leads to a high level of SWB and predicts SWB (Aknin, Hamlin, & Dunn, 2012;Oarga, Stavrova, & Fetchenhauer, 2015;Pareek & Jain, 2012).…”
Section: Internet Altruistic Behaviour and Subjective Wellbeingmentioning
confidence: 79%
“…Tian, Du, and Huebner (2015) revealed that altruistic behaviour was positively correlated with life satisfaction and positive affect. Findings reported by several empirical studies have also shown that altruistic behaviour leads to a high level of SWB and predicts SWB (Aknin, Hamlin, & Dunn, 2012;Oarga, Stavrova, & Fetchenhauer, 2015;Pareek & Jain, 2012).…”
Section: Internet Altruistic Behaviour and Subjective Wellbeingmentioning
confidence: 79%
“…This reciprocity helped the people affected by aphasia (both PWA and their families) to feel valued and gave them a sense of purpose. Helping others, not only being helped is significant for boosting well-being (Oarga, Stavrova, & Fetchenhauer, 2015). In addition, participants described personal attributes that facilitated them to live successfully with aphasia.…”
Section: Discussionmentioning
confidence: 99%
“…Combining these two lines of work would reveal whether certain people are more or less consistent in the type of help they prefer to provide and receive. Future work should consider both sides of the equation by examining features of the helper (e.g., through the HOI scales) and the helpseeker (e.g., their help-seeking preferences; Nadler & Chernyak-Hai, 2014;Tscharaktschiew & Rudolph, 2015), and how these interactions can lead to effective helping relationships and positive outcomes for all involved (e.g., well-being; Oarga, Stavrova, & Fetchenhauer, 2015).…”
Section: Discussionmentioning
confidence: 99%